X-linked FRMD7 gene mutation in idiopathic congenital nystagmus and its role in eye movement: A case report and literature review - Liu, Fanfei; Wang, Minjin; Liao, Meng; Liu, Longqian; Jiang, Xiaoshuang (Frontiers in Ophthalmology, 2023)
Background Idiopathic congenital nystagmus (ICN) is an inherited disorder characterized by uncontrollable binocular conjugating oscillation. X-linked idiopathic congenital nystagmus is one of the most prevalent types of ICN. Elucidation of the genetic mechanisms involved in ICN will enhance our understanding of its molecular etiology. Case presentation We report a girl with uncontrollable binocular oscillation and anomalous head posture, then presented a novel heterozygous missense variant (c.686G>T) within the mutation-rich region of the FERM domain containing 7 (FRMD7) gene in her family member. The girl received occlusion therapy and surgical operation which balanced her binocular vision and corrected the anomalous head posture. Conclusions This is the first report on a mutation (c.686G>T) caused the substitution of Arg (R) with Leu (L) at position 229 (p.R229L) of the FRMD7 protein in a patient with ICN.